PEMBELAJARAN ALQURAN HADIS DI MAN PAGAR ALAM - Defit Roly (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2017)
This study aims to determine the  learning of Alquran  and  Hadits  in Religious  Senior  High  School  students of Pagaralam. The  results  of this  study  used  for  several  strategies,  namely  balancing the  classical and  individual  learning approach which  are  arranged i practically  so it is easy to  be  learned, emphasizing the  ability of learners to  be  able  to read  the  Qur’an in tartil,  using  variations  of the  recitations theme of the  Qur’an so that  the  reading is not  boring, using the  system of sima’an (listening) so the  learners are able to justify or correct the  Qur’an recitation of other learners. The learning process  is also  done  by creating lesson  plans  by the  teacher in  charge  of teaching the  Qur’an. By providing matriculation, the  students are  expected to know in advance  before  they get a Qur’an lesson  in the  learning process  so that  they know more  about  what will be learned. With more  familiar  with what will be learned, the  students get a basic overview of the  entire subject  matter provided, organizing study groups,  and  the  development through extracurricular activities. Internal factors  which  may affect  the  learning of the  Qur’an is the  willingness  of students to  learn,  students’ interest towards learning the  Qur’an is not  maximized and  the  lack of motivation of students to learn  the  Qur’an further. External factors  are  the  parents and  families  who  are  very influential on  students’  ability to  read  the  Qur’an. Among families (parents) and  school  (teachers) has a role,  influence and  responsibility for the  success of the  Qur’an education at Religious  Senior  High  School  of Pagaralam